When I am big - Packard, Mary; Rader, Laura (Pleasantville, NY : Reader's Digest Children's Books, 1999)
A boy enjoys imitating his big brother and dreams of the day when he will be big as well.
Includes gold star reward stickers.
"Preschool-grade 1"--cover.
Keywords: Growth -- Fiction; Brothers -- Fiction; Stories in rhyme